Aberrant salience and fatigue as mediators between early life experiences and ideas of reference. Issue 1 (2nd January 2020) - León-Palacios, María De Gracia; Garrido-Fernández, Miguel; Senín-Calderón, Cristina; Perona-Garcelán, Salvador; Rodríguez-Testal, Juan Francisco
ABSTRACT: Introduction : This article reports on a mediational study performed from a proposal relating positive and negative indicators in clinical and nonclinical populations on a psychopathological severity continuum. We analyzed a mediation model of the development of vulnerability to psychosis, recalled threatening experiences, and submission to or devaluation by caregivers, in which aberrant salience and fatigue are the mediating variables on ideas of reference. Method : The sample consisted of 437 participants (295 healthy controls and 142 patients), and the study design was ex-post-facto, transversal, and multivariate. Results : Early threat, submission and devaluation experiences were found to be significantly related to ideas of reference and to the aberrant salience and fatigue variables. Aberrant salience and fatigue partially mediated the relationship between recalled adverse experiences with caregivers and the presence of ideas of reference. Conclusions : This study shows the importance of aberrant salience and fatigue in the development of Psychotic-like Experiences such as ideas of reference. The continuum model suggests that these processes may be analyzed in clinical and nonclinical populations.